РАСПРЕДЕЛЕНИЕ ГРАМПОЛОЖИТЕЛЬНЫХ БАКТЕРИЙ В ЦЕЛИННЫХ ПОЧВАХ РАВНИННОЙ ТЕРРИТОРИИ КАЗАХСТАНА (Experimental biology, 2017)
The article was studied the distribution of gram-positive bacteria in the virgin soils of the plains in Kazakhstan. The specific structure of gram-positive bacteria, the major soil types in Kazakhstan has been varied. In all types of soil bacteria, dominated by representatives of the genus Bacillus and Rhodococcus . In the gray-brown desert soils dominated by species ofthe Kazakhstan Bас. megaterium, Bac mycoides and Rh. aetherevorans. In the desert brown, light brown to medium soils in a large number of spesies found Bac. мegaterium и Rh. baikonurensis, and the black earth was dominated by Rh. erythropolis, Rh. aetherevorans, Rh. Baikonurensis, Bас. мegaterium.
Keywords: gram-positive bacteria; Bacillus; Rhodococcus